Evaluation of Chemo-Preventive Effect of Methanolic Fruit Extract of Cucumis melo var. agrestis on DEN-Induced HCC in Sprague Dawley Rats - Sivakumar, G; Devi, S Anjala (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim: To investigate chemo-preventive effect of methanolic fruit extract of Cucumis melo var. agrestis on DEN (diethyl-nitrosamine) induced hepatocellular carcinoma in Sprague Dawley rats. Materials and Methods: Five groups of rats randomly selected comprising of 6 animals on each group, all groups, except Group-1 were administered single dose of DEN (200 mg/kg, i.p. dissolved in PBS) for the induction of HCC and promoted by phenobarbital (0.05%) for 16 weeks. Group-I was administered only normal saline, however Group-3, 4 and were intervened by the standard (5-FU) and Test-1 and 2 by MECM. At the end of 16th week, overnight fasted rats were sacrificed under anaesthesia then blood samples and liver were collected to analyse morphological liver, to evaluate serum antioxidant, liver enzymatic, non-enzymatic, haematological parameters as well as to evaluate histopathology to assess the effect of standard (5-FU) as well as test (MECM) on DEN induced HCC in rats. Results: As in the case of Test-1 and 2 groups treated by low and high dose (200 mg/kg and 400 mg/kg) of MECM has showed only mild to moderate dose dependant effect on serum anti-oxidant as well as liver enzymatic and non-enzymatic activity. However, other parameter such as in body weight, liver morphology, tumour incidence, haematological as well as histopathology results with respect to standard drug (5-FU) was very poor. Conclusion: This study has demonstrated that MECM clearly lack its ability to act as a chemo-preventive agent, however the moderate antioxidant effect might place it as an effective adjuvant on the treatment of HCC.
Keywords: Diethyl-nitrosamine; Hepatocellular carcinoma; Methanolic fruit extract of Cucumis melo var. agrestis; 5-Fluro-uracil and Phosphate buffer solution